Tolerance synthesis of fastened metal-composite joints based on probabilistic and worst-case approaches. (July 2018) - Askri, Ramzi; Bois, Christophe; Wargnier, Hervé; Gayton, Nicolas
Abstract: Variabilities in geometrical and material properties occur systematically after manufacturing and joining operations on different parts of an assembly. The behaviour and structural performance of composite/composite or composite/metal fastened joints are particularly sensitive to some of these variabilities. Controlling the effect of variabilities by tolerancing uncertain parameters is therefore crucial to avoid the failure of the structure. However, performing a variability study is generally costly because a large number of configurations need to be evaluated, especially when the behaviour model of the system is a numerical one. This paper presents an approach for tolerance synthesis of uncertain parameters in fastened metal-composite joints. The low time-cost of the approach is ensured by using a reduced finite element model of the joints and a strategy to reduce the number of calculations. Both probabilistic and worst-case approaches for the propagation of uncertainties can be applied through the proposed tolerancing synthesis. An allowable tolerance value for an uncertain parameter can then be easily calculated by identifying an analytical law which links tolerance to a structural performance criterion. The robustness of the proposed approach is illustrated by its application to a 4-bolt metal-composite single-lap joint where several sources of variability are introduced (i.e. hole-location error, pin/hole clearance, fastener preload). Highlights: A tolerance synthesis of fastened joints based on probabilistic and worst-case approaches is proposed. A reduced finite element model is considered for the propagation of uncertainties. The approach is applied to tolerance hole-location errors in a metal-composite joint.